The yeast Wickerhamomyces anomalus acts as a predator of the olive anthracnose-causing fungi, Colletotrichum nymphaeae, C. godetiae, and C. gloeosporioides - Amorim-Rodrigues, Mariana; Brandão, Rogélio Lopes; Cássio, Fernanda; Lucas, Cândida (Frontiers in Fungal Biology, 2024)
Olive tree anthracnose is caused by infection with Colletotrichum fungi, which in Portugal are mostly C. nymphaeae, C. godetiae, and C. gloeosporioides s.s. Severe economic losses are caused by this disease that would benefit from a greener and more efficient alternative to the present agrochemical methods. Yeasts are serious candidates for pre-harvest/in field biocontrol of fungal infections. This work identified the yeast Wickerhamomyces anomalus as a strong antagonizer of the three fungi and studied in vitro this ability and its associated mechanisms. Antagonism was shown to not depend on the secretion of volatile compounds (VOCs), or siderophores or any other agar-diffusible compound, including hydrolytic enzymes. Rather, it occurred mostly in a cell-to-cell contact dependent manner. This was devised through detailed microscopic assessment of yeast-fungus cocultures. This showed that W. anomalus antagonism of the three Colletotrichum proceeded through (i) the adhesion of yeast cells to the phytopathogen hyphae, (ii) the secretion of a viscous extracellular matrix, and (iii) the emptying of the hyphae. Yeasts ultimately putatively feed on hyphal contents, which is supported by light microscopy observation of MB and PI co-culture-stained samples. Accordingly, numerous W. anomalus cells were observed packing inside C. godetiae emptied hyphae. This behaviour can be considered microbial predation and classified as necrotrophic mycoparasitism, more explicitly in the case of C. godetiae. The results support the prospect of future application of W. anomalus as a living biofungicide/BCA in the preharvest control of olive anthracnose.